Розробка технології комплексного легування рідкісних тугоплавких металів в процесі відновлення - Янко, Тарас Богданович; Овчинников, Олександр Володимирович (НТУ "ХПІ", 2015)
Проведений аналіз виробництва та визначені основні проблеми легування сплавів титану та цирконію. Проведено дослідження з розробки технології комплексного легування рідкісних тугоплавких металів титану та цирконію. Проведено термодинамічний аналіз для систем легування титану та цирконію. Визначені основні реакції процесів відновлення. Розроблено конструкції апаратів відновлення тетрахлориду цирконію та суміші тетрахлоридів титану та ванадію.

The analysis of the production and the main problems of alloying of titanium-based and zirconium-based alloys have been carried out. The research for elaboration of complex alloying technologies of rare refractory metals titanium and zirconium has been carried out. A technological scheme of alloyed titanium and zirconium sponge obtaining been developed. The optimal input methods of alloying elements to the process of getting alloyed sponged titanium and zirconium at the stage of recovery were set. Thermodynamic analysis of the alloying of titanium and zirconium sponged was performed. It have been developed a constructions of recovery apparatuses for zirconium tetrachloride and a mixture of titanium and vanadium tetrachlorides with aluminum, as well as the device for obtaining of a mixture of titanium and vanadium tetrachlorides with a specified vanadium content.
Elaboration of the complex alloying technology of rare refractory metals at the stage of recovery
Keywords: цирконій; алюміній; титан; ванадій; сплав; реакційна маса; zirconium; titanium; aluminum; vanadium; reaction mass